2014
DOI: 10.12659/msm.892957
|View full text |Cite
|
Sign up to set email alerts
|

Intra-Articular Adhesion Reduction after Knee Surgery in Rabbits by Calcium Channel Blockers

Abstract: BackgroundIntra-articular adhesion after knee surgery is a common and serious complication that presents a challenging problem for orthopedic surgeons. Verapamil (VP), a widely used calcium channel blocker, has been shown to prevent synthesis/secretion of extracellular matrix molecules. The object of this study was to investigate the effects of VP on the prevention of joint adhesion in post-surgery rabbits.Material/MethodsA controlled double-blinded study was conducted in 40 healthy New Zealand white rabbits d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 24 publications
0
5
0
1
Order By: Relevance
“…Although the effects of MMC in preventing collagen synthesis and scar formation were proved in the aforementioned studies, due to the toxicity of MMC, some researchers doubted that MMC would lead to an increased rate of infection [ 22 ]. A recent study provided clear evidence that all-trans retinoic acid (ATRA) prevents PF through the NF-κB signaling pathway [ 15 ] and another study showed the ability of azithromycin to prevent PF [ 7 ]. In the present study we found a similar effect of RPM in prevention of PF, as reflected by Rydell score and the anti-inflammatory and anti-fibrotic abilities of RPM also were as good as ATRA and azithromycin.…”
Section: Discussionmentioning
confidence: 99%
“…Although the effects of MMC in preventing collagen synthesis and scar formation were proved in the aforementioned studies, due to the toxicity of MMC, some researchers doubted that MMC would lead to an increased rate of infection [ 22 ]. A recent study provided clear evidence that all-trans retinoic acid (ATRA) prevents PF through the NF-κB signaling pathway [ 15 ] and another study showed the ability of azithromycin to prevent PF [ 7 ]. In the present study we found a similar effect of RPM in prevention of PF, as reflected by Rydell score and the anti-inflammatory and anti-fibrotic abilities of RPM also were as good as ATRA and azithromycin.…”
Section: Discussionmentioning
confidence: 99%
“…The detailed formation mechanism of intra-articular knee adhesion was not well represented in the literature. Fibroblastic activity exerts a key role in this process [ 6 , 7 , 11 ]. Fibroblast accumulation in the surgical area is considered to be caused by the activation of inflammatory activity, at which time the fibroblasts synthesize collagen and generate collagenous fibers.…”
Section: Discussionmentioning
confidence: 99%
“…Sterile conditions were created before surgery. The study model for intra-articular adhesion was based on previously published rat model protocols [ 4 , 7 , 8 ]. The animals were anesthetized using ketamine (50 mg/kg) and xylazine (10 mg/kg) via intra-peritoneal injection.…”
Section: Methodsmentioning
confidence: 99%
“…Assessment was based on a previously established visual score system [ 4 , 5 ]. Four weeks post-surgery, five rats were randomly selected from each group.…”
Section: Methodsmentioning
confidence: 99%